Risk factors for abdominal aortic aneurysm in general populations: A systematic review and meta-analysis - Pingzhen Zhang; Chunyan Liu; Jingjing Li; Huan Gao; Yuanyuan Fu; Wan Feng; Zhouzhen Chen; Xia Chen; Guiqin Wu (PLoS ONE, 2025)
Background Abdominal aortic aneurysm (AAA) has a high mortality rate after rupture. This study systematically explored the risk factors associated with AAA in the general population using a meta-analytic approach. Materials and methods We conducted a systematic search of PubMed, Embase, and Cochrane Library databases to identify relevant literature. The search was conducted through May 2025. Factors considered in more than three studies were included in the analysis. Odds ratios (ORs) with 95% confidence intervals (CIs) were used as effect estimates and all pooled analyses were performed using a random-effects model. Results Thirty-four studies reporting 34,551 AAA cases were selected for meta-analysis. Increased risk of AAA was associated with male (OR: 3.78; 95% CI: 2.80–5.10; P < 0.001), current or ever smoking (OR: 3.39; 95% CI: 2.57–4.48; P < 0.001), hypertension (OR: 1.31; 95% CI: 1.21–1.42; P < 0.001), dyslipidemia (OR: 1.33; 95% CI: 1.24–1.43; P < 0.001), coronary artery disease (OR: 1.81; 95% CI: 1.66–1.98; P < 0.001), cerebrovascular disease (OR: 1.32; 95% CI: 1.18–1.48; P < 0.001), peripheral vascular disease (OR: 1.67; 95% CI: 1.47–1.91; P < 0.001), chronic obstructive pulmonary disease (OR: 1.58; 95% CI: 1.31–1.90; P < 0.001), renal disease (OR: 1.91; 95% CI: 1.28–2.83; P = 0.001) and family history of AAA (OR: 2.26; 95% CI: 1.58–3.25; P < 0.001). However, diabetes mellitus was associated with a reduced risk of AAA (OR: 0.84; 95% CI: 0.74–0.95; P = 0.007). Furthermore, the risk of AAA was not affected by advanced age, alcohol intake, cancer, being overweight, or physical activity. The association between AAA risk and sex, smoking, hypertension, diabetes mellitus, renal disease, and a family history of AAA differs between Eastern and Western countries. Conclusions We systematically explored the risk factors for AAA. AAA represent a significant public health concern. Thus, early intervention and health education targeting these risk factors are necessary to prevent their occurrence. Registration: INPLASY2023120024